Electrode, preparation method thereof and lithium ion battery

By using a polymer/inorganic ceramic composite electrolyte system and carbon film current collector on the sulfur positive electrode and lithium negative electrode of the lithium sulfur battery, the problem of poor polysulfide shuttle and interface compatibility is solved, the cycle stability and safety performance of the battery are improved, and the process is simplified.

CN119920823APending Publication Date: 2025-05-02CHONGQING TALENT NEW ENERGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411382122.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The sulfur positive electrode in lithium-sulfur batteries has a problem of polysulfide shuttle, resulting in low cyclic stability and safety performance; the interface compatibility between the protective layer of the lithium negative electrode and metal lithium is poor, the ionic conductivity is low, and the process is complicated.

Method used

A polymer/inorganic ceramic composite electrolyte system is used as the protective layer for the sulfur positive electrode and the lithium negative electrode, and a protective layer is formed by plasma deposition to improve interface compatibility and ionic conductivity, and a carbon film is used as the current collector for the metal lithium negative electrode.

Benefits of technology

Effectively inhibit polysulfide shuttle, improve the cycle stability and safety performance of lithium-sulfur batteries, simplify the process, and reduce the battery weight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005070159470000191
    Figure BDA0005070159470000191
  • Figure BDA0005070159470000201
    Figure BDA0005070159470000201
  • Figure HDA0005070159480000011
    Figure HDA0005070159480000011
Patent Text Reader

Abstract

The invention relates to an electrode, a preparation method thereof and a lithium ion battery. According to the invention, the protective layer formed by the polymer and the inorganic material is formed on the sulfur positive electrode and / or the metal lithium negative electrode, so that the problems of polysulfide shuttling and relatively low interfacial compatibility and ionic conductivity between the metal lithium negative electrode and the protective layer are solved. When the composite material is used for a sulfur positive electrode, the problem of shuttling of polysulfide can be solved; when the metal lithium negative electrode material is used for a lithium negative electrode, the problems of low interfacial compatibility and low ionic conductivity between the metal lithium negative electrode and a protective layer can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to an electrode and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium metal has become a strong competitor for the negative electrode of the next generation of ultra-high energy density batteries due to its ultra-high gram capacity and low potential. However, due to the active chemical properties of lithium metal, it is easy to react with the electrolyte, resulting in unstable structure and composition of the SEI film formed, and accompanied by the generation of lithium dendrites, which greatly reduces the cycle stability and safety performance of lithium batteries and limits the further development of high energy density batteries. In order to solve the current problems of lithium negative electrodes, functional electrolyte additives can form a relatively stable SEI film in situ, but the SEI film generated in situ by the electrolyte additive method has unstable chemical composition, uneven structure, and weak mechanical properties. The SEI film formed in situ by this method still cannot meet people's requirements for lithium metal batteries.

[0003] In contrast, the artificially constructed protective layer on the surface of the lithium negative electrode has the characteristics of relatively uniform chemical composition, spatial distribution and mechanical properties, so some progress has been made in the protection of metallic lithium negative electrodes. The artificially constructed protective layer must have high ionic conductivity, low electronic conductivity, high mechanical modulus and stable chemical properties. Currently, polymers, inorganic solid electrolytes (such as Li3PO4), carbon material coatings, metal oxides and sulfides are more commonly used. However, these materials and their construction methods currently have poor interface compatibility, low ionic conductivity at the interface, and complex and time-consuming processes, which are not suitable for large-scale production.

[0004] In addition, lithium-sulfur batteries use metallic lithium as the negative electrode and sulfur as the positive electrode, where the specific capacity of metallic lithium is 3860mAh / g and the specific capacity of sulfur is 1670mAh / g, making the theoretical mass energy density of lithium-sulfur batteries reach 2600Wh / Kg and the theoretical volume energy density reach 2800Wh / Kg. However, when lithium-sulfur batteries are discharged, sulfur will first form polysulfides that are soluble in the electrolyte. The polysulfides shuttle to the surface of the metallic lithium negative electrode and produce side reactions with metallic lithium, resulting in irreversible loss of active substances, greatly reducing the cycle life of lithium-sulfur batteries. In addition, lithium is consumed, resulting in loss of active lithium and damage to the surface of metallic lithium, which can easily lead to the formation of lithium dendrites, greatly reducing the electrochemical performance of lithium-sulfur batteries and causing great safety hazards.

[0005] Generally, a layer of functional polymer film is added between the sulfur cathode and the separator to block the shuttling of polysulfides. However, this method is relatively complicated. In order to achieve good interface performance, a three-layer structure is generally used. Moreover, this method cannot be industrialized and can only remain in the experimental stage. Summary of the invention

[0006] Problem that the invention aims to solve

[0007] From the above, it can be seen that for the sulfur positive electrode, there is a problem that the method of adding a functional polymer film to block the shuttling of polysulfide is complicated and cannot be industrialized. For the lithium negative electrode, there is a problem that the interface compatibility between the protective layer and the metal lithium negative electrode is poor, the ion conductivity is low, the process is complicated, and the battery weight is heavy.

[0008] Solutions for solving problems

[0009] To solve the above problems, the present invention provides a polymer / inorganic ceramic composite electrolyte system, which can solve the problem of polysulfide shuttling when used in sulfur positive electrode; and can solve the problem of low interfacial compatibility and ion conductivity between the metal lithium negative electrode and the protective layer when used in lithium negative electrode. In addition, the present invention proposes to use a metal lithium negative electrode with a carbon film as a current collector, which can simultaneously improve the cycle stability of the metal lithium negative electrode and reduce the overall battery mass.

[0010] Specifically, the present invention provides an electrode, which includes a sulfur positive electrode and a protective layer on the surface of the sulfur positive electrode, wherein the protective layer is formed of a composite material, and the composite material includes a polymer and an inorganic material.

[0011] According to the electrode described above, the polymer includes one or more of fluorine-containing polymers, polyethylene oxide, polyurethane, poly(meth)acrylates, polyacrylonitrile, polyethyleneimine, polycyanoethyl acrylate, polycarbonates, polymalonates, and polysuccinates.

[0012] According to the above-mentioned electrode, the fluorine-containing polymer includes one or more of polyvinylidene fluoride, polyvinylidene fluoride, polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-chlorotrifluoroethylene, and perfluorosulfonic acid resin; the poly (meth) acrylates include one or more of polymethyl acrylate, polymethyl methacrylate, polyethyl acrylate, polyethyl methacrylate, polybutyl acrylate, and polybutyl methacrylate; the polycarbonates include one or more of polyvinyl carbonate, polypropylene carbonate, polytrimethyl carbonate, and polyethylene carbonate.

[0013] The present invention also provides an electrode, which comprises a metal lithium negative electrode and a protective layer on the surface of the metal lithium negative electrode.

[0014] The protective layer is formed of a composite material, the composite material includes a polymer and an inorganic material, and the polymer includes one or more of polyethyleneimine, polyethylcyanoacrylate, polymalonates, and polysuccinates.

[0015] According to the electrode described above, the polymalonates include one or more of polypentylene malonate, polyethylene malonate, polypropylene malonate, and polyhexylene malonate; the polysuccinates include one or more of polyethylene succinate, polypropylene succinate, polyethylene succinate, and polybutylene succinate.

[0016] According to the electrode described above, the inorganic material includes an inorganic ceramic composite electrolyte, and the inorganic ceramic composite electrolyte includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte;

[0017] Preferably, the oxide solid electrolyte is selected from one or more of lithium lanthanum zirconium oxide, lanthanum titanate lithium oxide, tantalum-doped lithium lanthanum zirconium oxide, aluminum-doped lithium lanthanum zirconium oxide, and lithium germanium aluminum phosphate;

[0018] The sulfide solid electrolyte is selected from one or more of lithium germanium phosphorus sulfur compounds and lithium phosphorus sulfur chloride compounds.

[0019] According to the electrode described above, the inorganic material accounts for 5% to 95% by mass, preferably 70% to 90% by mass, of the total mass of the polymer and the inorganic material.

[0020] According to the above electrode, the thickness of the protective layer is 3 μm to 250 μm.

[0021] The present invention provides a sulfur positive electrode, which comprises the above-mentioned electrode and a positive electrode current collector, wherein the positive electrode current collector is aluminum foil, carbon-coated aluminum foil, porous aluminum foil or porous carbon-coated aluminum foil.

[0022] The present invention also provides a lithium negative electrode, which comprises the electrode described above and a negative electrode current collector, wherein the negative electrode current collector is a copper foil or a carbon film.

[0023] The present invention further provides a method for preparing an electrode, which comprises the following steps:

[0024] Step S1, mixing a polymer and an inorganic material to prepare a composite material; and

[0025] Step S2, forming a protective layer formed of the composite material on the surface of the metal lithium negative electrode or the sulfur positive electrode.

[0026] According to the preparation method described above, in step S2, the protective layer is formed by a solution method, a plasma deposition method, a magnetron sputtering method, a pulsed laser sputtering method, a physical deposition method or a chemical vapor deposition method.

[0027] According to the preparation method described above, the solution method is selected from any one of a plasma gas spraying method, a compressed gas spraying method, a high-pressure spraying method, and a plasma source evaporation solution method.

[0028] According to the preparation method described above, the plasma deposition method is a suspension plasma deposition method or a plasma-assisted electron beam deposition method.

[0029] According to the preparation method described above, in the suspension plasma deposition method, the suspension includes the polymer, the inorganic material and a solvent; the solvent includes one or more of N,N-dimethylformamide, dimethyl sulfoxide and acetone.

[0030] According to the above-mentioned preparation method, in the suspension plasma deposition method, the ejection speed of the suspension is 10-40cm 3 / min; the distance between the plasma jet nozzle and the substrate is 20-150mm.

[0031] According to the preparation method described above, in the suspended plasma deposition method, the plasma is generated in any one of the following ways: DC glow discharge plasma, wherein the excitation power supply voltage is 500V-1500V; pulsed glow discharge plasma, wherein the pulse width is 30-150μs and the peak voltage is 400V-600V; dielectric barrier plasma, wherein the high-voltage excitation power supply is a sinusoidal AC power supply or a nanosecond pulse high-voltage power supply; radio frequency plasma, wherein the frequency of the AC glow discharge is higher than 100kHz, and the radio frequency plasma includes capacitively coupled radio frequency plasma and inductively coupled radio frequency plasma, wherein the discharge voltages of the inductively coupled radio frequency plasma and the capacitively coupled radio frequency plasma are 100V-1000V and the pressures are 1Pa-100Pa respectively; microwave plasma, wherein the microwave frequency for generating the plasma is 300MHz-10GHz.

[0032] According to the preparation method described above, in the plasma-assisted electron beam deposition method, the target material is the composite material; the electron beam current is less than 5A, the voltage is less than 2kV, and the distance from the target material to the substrate is 5mm-100mm.

[0033] According to the preparation method described above, in the plasma-assisted electron beam deposition method, the plasma source is selected from any one of the following: capacitively coupled plasma, which generates plasma at a frequency higher than 100kHz); DC glow discharge plasma, in which the excitation power supply voltage is 500V-1500V; pulsed glow discharge plasma, in which the pulse width is 30μs-150μs and the peak voltage is 400V-600V; dielectric barrier plasma, in which the high-voltage excitation power supply is a sinusoidal AC power supply or a nanosecond pulse high-voltage power supply; microwave plasma, in which the microwave frequency of the plasma is 300MHz-10GHz.

[0034] The present invention further provides a lithium ion battery, which comprises the electrode described above or an electrode prepared by the above preparation method.

[0035] Effects of the Invention

[0036] The above technical solution of the present invention has the following beneficial effects:

[0037] (1) When the polymer / inorganic ceramic composite solid electrolyte material of the present invention is used for the sulfur positive electrode, the material fully combines the flexible interface of the polymer solid electrolyte with the high ionic conductivity of the inorganic ceramic solid electrolyte, which can not only allow lithium ions to pass smoothly, but also inhibit the shuttling effect of polysulfides in the electrolyte and reduce the side reactions between polysulfides and the lithium negative electrode through the steric effect and the chemical adsorption of the functional groups of the polymer and the inorganic material, thereby improving the safety and cycle stability of the lithium-sulfur battery as a whole.

[0038] (2) When the polymer / inorganic ceramic composite electrolyte system of the present invention is used for lithium negative electrode, it better solves the problem of interface compatibility between the protective layer and the metal lithium negative electrode and the problem of low ion conductivity.

[0039] (3) During electrode preparation, a plasma deposition method is used to deposit the protective layer. This method has a fast deposition speed and can achieve large-area film deposition in a short time. It has high production efficiency and a wide range of applications, so the range of substrate materials is relatively wide.

[0040] (4) The metal lithium negative electrode of the present invention using a carbon film as a current collector can reduce the weight of the entire battery and improve the cycle stability of the metal lithium negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 A schematic diagram showing the deposition process of the suspension plasma deposition method.

[0042] Figure 2 A schematic diagram showing the deposition process of plasma-assisted electron beam deposition. DETAILED DESCRIPTION

[0043] The following describes the embodiments of the present invention, but the present invention is not limited thereto. The present invention is not limited to the various structures described below, and various changes can be made within the scope of the invention claim, and the embodiments obtained by appropriately combining different embodiments and appropriately combining the technical means disclosed in the embodiments are also included in the technical scope of the present invention. In addition, all the documents recorded in this specification are cited in this specification as references.

[0044] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0045] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0046] In this specification, unless otherwise specified, the word "multiple" in "multiple", "multiple", "plurality", etc. means a numerical value of 2 or more.

[0047] In the present specification, the term “substantially”, “substantially” or “essentially” means that the error is less than 5%, or less than 3%, or less than 1% compared with a relevant perfect standard or theoretical standard.

[0048] In this specification, unless otherwise specified, "%" means mass percentage.

[0049] In this specification, if "room temperature" or "normal temperature" appears, the temperature may generally be 25±5°C.

[0050] In this specification, the meanings of “may” or “can” include both existence and non-existence, and both performing a certain process and not performing a certain process.

[0051] As used herein, “optional” and “optionally” mean that the subsequently described event or circumstance may or may not occur, and that the description includes instances where the event occurs and instances where it does not occur.

[0052] The term "comprising" and any variations thereof in the specification and claims of the present invention and the above drawings are intended to cover non-exclusive inclusions. For example, a process, method or system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.

[0053] In this specification, the references to "some / certain / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0054] <First aspect>

[0055] A first aspect of the present invention provides an electrode comprising a sulfur cathode and a protective layer on a surface of the sulfur cathode, wherein the protective layer is formed of a composite material comprising a polymer and an inorganic material.

[0056] In this aspect, the polymer includes one or more of fluorine-containing polymers, polyethylene oxide, polyurethane, poly(meth)acrylates, polyacrylonitrile, polyethyleneimine, polyethylcyanoacrylate, polycarbonates, polymalonates, and polysuccinates.

[0057] Among them, the fluorine-containing polymer includes one or more of polyvinylidene fluoride, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-chlorotrifluoroethylene, perfluorosulfonic acid resin, and lithiated perfluorosulfonic acid resin; the poly (meth) acrylates include one or more of polymethyl acrylate, polymethyl methacrylate, polyethyl acrylate, polyethyl methacrylate, polybutyl acrylate, and polybutyl methacrylate; the polycarbonates include one or more of polyvinylene carbonate, polypropylene carbonate, polytrimethyl carbonate, and polyethylene carbonate.

[0058] The polymalonates include one or more of polypentylene malonate, polyethylene malonate, polypropylene malonate, and polyhexylene malonate; the polysuccinates include one or more of polyethylene succinate, polypropylene succinate, polyethylene succinate, and polybutylene succinate.

[0059] The inorganic material includes an inorganic ceramic composite electrolyte, and the inorganic ceramic composite electrolyte includes one or more of lithium lanthanum zirconium oxide (LLZO), lanthanum titanate lithium oxide, tantalum-doped lithium lanthanum zirconium oxide, aluminum-doped lithium lanthanum zirconium oxide, lithium germanium phosphosulfur compound, lithium phosphosulfur chloride, and lithium germanium aluminum phosphate.

[0060] In this aspect, the inorganic material accounts for 5% to 95% by mass, preferably 70% to 90% by mass, of the total mass of the polymer and the inorganic material. For example, it may be 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95% by mass, etc.

[0061] The thickness of the protective layer is 3 μm to 250 μm, preferably 3 μm to 20 μm, for example, 3 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 35 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, 220 μm, 250 μm, etc. The thickness can be controlled by the deposition time in the plasma deposition process described later. If the thickness is too thin, the coating may not completely cover the sulfur surface, and if the coating is too thick, the impedance may be too high.

[0062] In the present invention, a polymer / inorganic ceramic composite material is deposited on the surface of the sulfur positive electrode to inhibit the shuttling effect of polysulfides in the electrolyte when the lithium-sulfur battery is working, reduce the side reaction between polysulfides and the lithium negative electrode, and thus improve the overall safety and cycle stability of the lithium-sulfur battery. The composite solid electrolyte combines the advantages of good interface compatibility between polymer materials and positive electrode materials and high ionic conductivity of inorganic solid electrolytes; at the same time, it can not only allow lithium ions to pass smoothly, but also limit the diffusion of polysulfides through steric effects and chemical adsorption of functional groups of polymers and inorganic materials, thereby improving the cycle stability and safety of lithium-sulfur batteries.

[0063] The present invention also provides a sulfur positive electrode, which comprises the above-mentioned electrode and a positive electrode current collector, wherein the current collector is aluminum foil, carbon-coated aluminum foil, porous aluminum foil or porous carbon-coated aluminum foil.

[0064] Using porous carbon-coated aluminum foil as the current collector can effectively increase the amount of active material loaded on the positive electrode current collector and can fully utilize the liquid electrolyte in the lean liquid state.

[0065] In some specific embodiments of the present invention, the sulfur positive electrode includes the following components: elemental sulfur with a particle size of 50 μm-300 μm and a mass fraction of 60%-70%; a conductive agent, which can be selected from one or more of carbon nanotubes (CNT), carbon fibers, conductive carbon black (super P), superconducting carbon black (BP2000), Ketjenblack (Carbon ECP, Carbon ECP 600JD, Ketjenblack EC 300J, Ketjenblack EC 600JD), conductive graphite, and acetylene black, and the content of the conductive agent is 10% to 30% by mass; a binder, which can be selected from one or more of an oily binder PVDF, polyethylene oxide PEO, carboxymethyl cellulose CMC / styrene-butadiene rubber SBR (mass ratio of 0-1), and polyacrylic acid PAA, and the content of the binder is 8% to 10% by mass. The current collector can be selected from one of aluminum foil (8μm-16μm), carbon-coated aluminum foil (aluminum foil substrate thickness is 8μm-16μm, single-sided coating thickness is 1μm-2μm), porous aluminum foil (pore size is 1μm-10μm, aluminum foil thickness is 8μm-16μm), and porous carbon-coated aluminum foil (pore size is 1μm-10μm, aluminum foil thickness is 8μm-16μm, and single-sided carbon coating thickness is 1μm-2μm).

[0066] In some specific embodiments, the preparation method of the sulfur positive electrode is: first, the elemental sulfur is mixed with one or more of CNT, BP2000, and Ketjen black for ball milling, the mass ratio of sulfur is 75%-80%, the ball-to-material ratio is 6:1-10:1, the ball milling time is 4h-24h, and then placed in a tubular furnace, inert gas protection, 155°C for 24 hours; after cooling, take out, mix the calcined material with the remaining one or more conductive agents, and then add a binder. The final mass fraction of elemental sulfur is 60%-70%. Then, a protective layer can be formed on the sulfur positive electrode.

[0067] <Second Aspect>

[0068] A second aspect of the present invention provides a lithium negative electrode, comprising a metal lithium negative electrode and a protective layer on the surface of the metal lithium negative electrode, wherein the protective layer is formed of a composite material, and the composite material comprises a polymer and an inorganic material.

[0069] In this aspect, the polymer includes one or more of polyethyleneimine, polyethylcyanoacrylate, polymalonates and polysuccinates.

[0070] The polymalonates include one or more of polypentylene malonate, polyethylene malonate, polypropylene malonate, and polyhexylene malonate; the polysuccinates include one or more of polyethylene succinate, polypropylene succinate, polyethylene succinate, and polybutylene succinate.

[0071] The inorganic material in the present invention is the same as that in the above-mentioned <First Aspect> and will not be described in detail here.

[0072] The inorganic material accounts for 5% to 95% by mass, preferably 70% to 90% by mass, of the total mass of the polymer and the inorganic material. For example, it may be 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95% by mass, etc.

[0073] The thickness of the protective layer is 3 μm to 250 μm, preferably 3 μm to 20 μm, for example, 3 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 35 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, 220 μm, 250 μm, etc. The thickness can be controlled by the deposition time in the plasma deposition process described later. If the thickness is too thin, the coating may not be able to completely cover the surface of the metallic lithium, and if the coating is too thick, the impedance may be too high.

[0074] The present invention uses a polymer / inorganic ceramic composite electrolyte as a protective layer on the surface of the metal lithium negative electrode to inhibit the side reactions between the metal lithium and the electrolyte and the active material, inhibit the generation and growth of lithium dendrites, and improve the safety and cycle stability of the metal lithium battery. The composite solid electrolyte combines the advantages of good interface compatibility between polymer materials and lithium negative electrodes and high ionic conductivity of inorganic solid electrolytes, and can simultaneously improve the interface compatibility of the lithium negative electrode protective layer and improve ionic conductivity.

[0075] The present invention also provides a metal lithium negative electrode, which comprises a metal lithium sheet, a metal lithium negative electrode with a copper foil as a current collector, and a metal lithium negative electrode with a carbon film as a current collector.

[0076] When copper foil is used as the current collector for the metal lithium negative electrode, the overall weight of the battery will increase and the battery energy density will be reduced. The density of the carbon film is much lower than that of copper. Therefore, the metal lithium negative electrode with carbon film as the current collector can simultaneously improve the cycle stability of the metal lithium negative electrode and reduce the overall battery mass, which is preferred. Lithium with carbon film as the current collector is already available and can be purchased. The carbon film is prepared with carbon nanotubes as raw materials and has a three-dimensional conductive structure. It can effectively provide electron channels, allowing lithium metal to be deposited more evenly and improving the cycle stability of metal lithium negative electrode batteries.

[0077] In addition, using metallic lithium with a three-dimensional carbon film as the current collector as the negative electrode of the lithium-sulfur battery, the three-dimensional structure of the current collector can effectively reduce the local current on the negative electrode, reduce the uneven deposition of lithium, and inhibit the growth of lithium dendrites, which helps to improve the cycle stability and safety performance of the lithium-sulfur battery.

[0078] In some specific embodiments of the present invention, the metal lithium negative electrode includes a metal lithium sheet (thickness 20μm-300μm), a metal lithium negative electrode with a copper foil as a current collector (wherein the copper foil has a thickness of 4μm-20μm, and the metal lithium has a thickness of 20μm-300μm), and a metal lithium negative electrode with a carbon film as a current collector (wherein the carbon film has a thickness of 4μm-20μm, and the metal lithium has a thickness of 20μm-300μm).

[0079] <Third Aspect>

[0080] A third aspect of the present invention provides a method for preparing an electrode, comprising the following steps:

[0081] Step S1, mixing a polymer and an inorganic material to prepare a composite material; and

[0082] Step S2, forming a protective layer formed of the composite material on the surface of the metal lithium negative electrode or the sulfur positive electrode.

[0083] In step S1, the polymer and the inorganic material are mixed and mechanically ball-milled to obtain a composite material. The types and contents of the polymer and the inorganic material in this aspect are the same as those in the first aspect, so they are not described here in detail.

[0084] In step S2 , the protective layer may be formed by a solution method, a plasma deposition method, a magnetron sputtering method, a pulsed laser sputtering method, a physical deposition method or a chemical vapor deposition method.

[0085] The solution method can be selected from any one of plasma gas spraying, compressed gas spraying, high pressure spraying, and plasma source evaporation solution method. The plasma deposition method can be a suspended plasma deposition method or a plasma assisted electron beam deposition method. The preparation method of the electrode is described below using the plasma deposition method as an example.

[0086] In the suspension plasma deposition method, the suspension includes the polymer, the inorganic material and a solvent.

[0087] There is no special requirement for the solvent, as long as it can disperse or dissolve the polymer, but the boiling point of the solvent cannot be too high. In the present invention, the solvent may include one or more of N,N-dimethylformamide, dimethyl sulfoxide (DMSO), and acetone. The solid content in the suspension is 2% to 15% by mass.

[0088] Figure 1 Schematic diagram of the deposition process of suspended plasma deposition is shown. Figure 1 As shown, in the suspended plasma deposition method, plasma gas is introduced into the plasma chamber to pass through the plasma generator ( Figure 1The invention relates to a method for preparing a polymer / inorganic ceramic precursor suspension. The method comprises: generating plasma by introducing a carrier gas into the polymer / inorganic ceramic precursor suspension so that the suspension enters the plasma chamber. Under the action of the plasma flow, the polymer / inorganic ceramic precursor suspension is deposited on the substrate through the plasma jet orifice to form a protective layer. In the present invention, the carrier gas may be argon.

[0089] In suspension plasma deposition, the more important parameters are: (1) the flow rate of the suspension carrier gas, which can control the speed at which the suspension precursor enters the plasma chamber; (2) the energy of the plasma generator: the energy of the plasma generator should not be too high. Higher plasma energy will cause excessive cross-linking of the polymer, resulting in reduced polymer film-forming properties and reduced interface performance with the sulfur positive electrode. Higher plasma energy will cause phase transformation of the ceramic part in the composite solid electrolyte, reducing ionic conductivity, which is related to the excitation power supply voltage in DC glow discharge, the pulse width and peak voltage in pulsed glow discharge, the discharge frequency in radio frequency plasma, and the frequency in inductively coupled radiation and microwave plasma; (3) the distance between the plasma jet and the substrate (hereinafter referred to as the substrate distance). The substrate distance also affects the interface performance of the composite solid electrolyte and the ionic conductivity of the body to a certain extent. The selection of the above parameters is related to the types of polymers and inorganic ceramic precursors used.

[0090] In the present invention, the spraying speed of the suspension is set to 10-40cm 3 / min; the distance between the plasma jet port and the substrate was set to 20-150mm.

[0091] In the suspended plasma deposition method, the plasma is generated in any one of the following ways: DC glow discharge plasma, wherein the excitation power supply voltage is 500V-1500V; pulsed glow discharge plasma, wherein the pulse width is 30-150μs and the peak voltage is 400V-600V; dielectric barrier plasma, wherein the high-voltage excitation power supply is a sinusoidal AC power supply or a nanosecond pulse high-voltage power supply; radio frequency plasma, wherein the frequency of the AC glow discharge needs to be higher than 100kHz, usually 13.56MHz, and the radio frequency plasma includes capacitively coupled radio frequency plasma and inductively coupled radio frequency plasma, wherein the discharge voltages of the inductively coupled radio frequency plasma and the capacitively coupled radio frequency plasma are 100V-1000V and the pressures are 1Pa-100Pa respectively; microwave plasma, wherein the microwave frequency for generating the plasma is 300MHz-10GHz.

[0092] The main gas of the plasma gas composition is Ar, and the auxiliary gas is hydrogen, and the hydrogen content is less than or equal to 5% by volume. The gas flow rate is controlled so that the pressure in the chamber is maintained at 0.1-100 Pa during the plasma treatment, and the plasma deposition time is 1 min-180 min, for example, 1 min, 5 min, 10 min, 30 min, 60 min, 80 min, 100 min, 150 min, 180 min, etc.

[0093] Figure 2 Schematic diagram of plasma-assisted electron beam deposition is shown. Figure 2 As shown, an electron beam is generated by an electron gun to heat and evaporate the target material, a plasma source is introduced into the chamber, and a plasma discharge is formed by passing electricity above and between the target material to increase the density of charged ions. Subsequently, a bias voltage is applied between the substrate and the target material, and the electric field accelerates the charged ions, thereby depositing on the substrate.

[0094] In plasma-assisted electron beam deposition, the more important parameters are: (1) the power of the electron beam generator, which determines the speed at which the target material mixture enters the deposition chamber; (2) the energy of the plasma generator is one of the key parameters, which is mainly related to the frequency of the generator in capacitive coupling, to its excitation power supply voltage in DC glow discharge, to its peak voltage in pulsed glow discharge, to the high-voltage excitation power supply frequency and voltage in dielectric barrier plasma, and to its frequency in microwave plasma; (3) the distance from the target material to the substrate (hereinafter referred to as "substrate distance"). The principles of parameters (2) and (3) are consistent with those of suspended plasma deposition and need to be determined based on the type of polymer / inorganic ceramic substrate selected.

[0095] In the plasma-assisted electron beam deposition method, the target material is a composite material made of polymer and inorganic material. The powdered solid of the mixture of polymer and inorganic ceramic is mechanically ball-milled (ball milling plays a role of full mixing, and there is no excessive requirement for particle size) for a period of time and then placed in a ceramic boat.

[0096] During deposition, the electron beam current is less than 5A, the voltage is less than 2kV, and the distance from the target to the substrate is 5mm-100mm.

[0097] In the plasma-assisted electron beam deposition method, the plasma source is selected from any of the following: capacitively coupled plasma, where the frequency of plasma generation needs to be higher than 100kHz, usually 13.56MHz; DC glow discharge plasma, where the excitation power supply voltage is 500V-1500V; pulsed glow discharge plasma, where the pulse width is 30μs-150μs and the peak voltage is 400V-600V; dielectric barrier plasma, where the high-voltage excitation power supply is a sinusoidal AC power supply or a nanosecond pulse high-voltage power supply; microwave plasma, where the microwave frequency of plasma generation is 300MHz-10GHz. The power here depends on the power of the electron beam generator, and the power of the plasma generator is twice the power of the electron beam generator.

[0098] The deposition speed of plasma deposition method is fast, and large-area film deposition can be achieved in a short time, with high production efficiency; it has a wide range of applications and can be used for the deposition of inorganic ceramics, metals and organic films; the substrate selection range is wide and there are no special requirements for the shape, including planar and cylindrical shapes can be used as substrates in plasma deposition; the substrate temperature can be kept lower by adjusting the circulating condensation system, so the range of substrate materials is wide.

[0099] In addition, during the plasma deposition process, the organic part will undergo a chemical reaction, so this method can be used to achieve the in-situ polymerization and cross-linking of the polymer solid electrolyte, thereby achieving better interface fusion between the protective layer and the lithium negative electrode.

[0100] <Fourth Aspect>

[0101] A fourth aspect of the present invention provides a lithium ion battery, comprising the lithium negative electrode of the above <first aspect> and the sulfur positive electrode of the <second aspect> or an electrode prepared by the preparation method of the above <third aspect>.

[0102] The protected lithium metal battery is used for the preparation of high energy density batteries, including lithium-sulfur / selenium (Li-S / Se) batteries, wherein the selenium (Se) content is 0 mass % to 100 mass %, lithium-LiNi x Co y Mn z O2 (x, y, z are each less than or equal to 1, and x+y+z=1) battery, lithium-lithium iron phosphate battery, lithium-lithium cobalt oxide battery, etc.

[0103] Example

[0104] The present invention will be described in detail below by way of examples. The examples of the embodiments are intended to explain the present invention and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0105] Example 1

[0106] Preparation of sulfur cathode

[0107] The sulfur positive electrode is prepared according to the mass ratio of sulfur: super P: CNT: PVDF = 7:2:1:1. The current collector is an oil-based carbon-coated porous aluminum foil, where the thickness of the aluminum foil is 8-16μm, and the thickness of the carbon coating on both sides is 2-4μm. The current carrying capacity of the positive electrode sheet is 12-18mg / cm 2 The size of the positive electrode sheet is 2.8-20.8cm in length and 1.8cm-15.3cm in width.

[0108] Formation of protective layer (plasma-assisted electron beam deposition)

[0109] The PVDF / LLZO powder was mechanically ball-milled for 1 h, wherein the content of LLZO was 80% by mass and the ball-to-material ratio was 6:1. Then, it was placed in a porcelain boat, put into a plasma generator, and evacuated to 10 -3 Pa, turn on the power of the plasma generator, here it is a capacitive coupled plasma, the frequency is 13.56MHz, the carrier gas is argon, after waiting for 5 minutes, turn on the electron beam evaporation equipment for current modulation 4A, adjust the voltage to about 1kV, use the sulfur cathode sheet prepared as above as the substrate, control its temperature to room temperature, the substrate distance is 50mm, and deposit for 0.5h. After completion, take out the sulfur cathode sheet with the coating.

[0110] The coated sulfur positive electrode sheet and the copper-lithium composite tape with a thickness of 200 μm were prepared into a laminated battery in a "Z"-shaped laminated manner, wherein the diaphragm was a PE diaphragm coated with Al2O3 or ZrO2 on the surface, and the electrolyte was a solution of ethylene glycol dimethyl ether DME / 1,3-dioxolane DOL=1:1 (volume ratio), 1 mol / L lithium bistrifluoromethanesulfonyl imide (LiTFSI) and 1 mass% LiNO3, wherein the number of negative electrode sheets was 5 and the number of positive electrode sheets was 4. In the copper-lithium composite tape, the thickness of the copper foil was 6 μm, and the thickness of the single-side lithium foil was 100 μm.

[0111] Example 2

[0112] Preparation of the Sulfur Cathode Referring to Example 1, a protective layer was formed by suspension plasma deposition as follows.

[0113] PVDF and LLZO powders were dissolved in a mixture of DMSO / acetone (volume ratio 70 / 30), in which the LLZO ratio was 90% by mass, the solid content of the whole system was 4% by mass, and the suspension system was stirred at a flow rate of 30 cm 3 The argon gas is brought into the plasma chamber at a speed of 10 / min, and the chamber pressure is maintained at 10 -3 Pa, the plasma torch energy is 50kW, the sulfur positive electrode prepared as above is used as the substrate, the substrate distance is 30mm, and the deposition is 0.2h to obtain a sulfur positive electrode sheet with a coating on the surface, which is prepared into a laminated battery in a "Z"-type laminated manner with a copper-lithium composite belt, wherein the total thickness of metallic lithium in the copper-lithium composite belt is 200μm (the thickness of the lithium sheet on one side is 100μm), and the thickness of the copper foil is 6μm, wherein the diaphragm adopts a PE diaphragm coated with Al2O3 or ZrO2 on the surface, and the electrolyte is a solution of DME / DOL=1:1 (volume ratio), 1mol / L lithium bistrifluoromethanesulfonyl imide (LiTFSI) and 1% LiNO3 by mass, wherein the number of negative electrode sheets is 5 and the number of positive electrode sheets is 4 correspondingly.

[0114] Example 3

[0115] The difference from Example 1 is that the content of the solid electrolyte LLZO is adjusted to 90 mass %.

[0116] Example 4

[0117] The difference from Example 1 is that the content of the solid electrolyte LLZO is adjusted to 70 mass %.

[0118] Example 5

[0119] The difference from Example 1 is that the content of the solid electrolyte LLZO is adjusted to 60 mass %.

[0120] Example 6

[0121] The difference from Example 1 is that the content of the solid electrolyte LLZO is adjusted to 50 mass %.

[0122] Example 7

[0123] The difference from Example 1 is that the content of the solid electrolyte LLZO is adjusted to 40 mass %.

[0124] Example 8

[0125] The difference from Example 1 is that the content of the solid electrolyte LLZO is adjusted to 30 mass %.

[0126] Example 9

[0127] The difference from Example 1 is that the content of the solid electrolyte LLZO is adjusted to 20 mass %

[0128] Example 10

[0129] The difference from Example 1 is that the content of the solid electrolyte LLZO is adjusted to 10% by mass.

[0130] Embodiment 11

[0131] The difference from Example 2 is that the content of the solid electrolyte LLZO is adjusted to 80 mass %.

[0132] Example 12

[0133] The difference from Example 2 is that the content of the solid electrolyte LLZO is adjusted to 70 mass %.

[0134] Example 13

[0135] The difference from Example 2 is that the content of the solid electrolyte LLZO is adjusted to 60 mass %.

[0136] Embodiment 14

[0137] The difference from Example 2 is that the content of the solid electrolyte LLZO is adjusted to 50 mass %.

[0138] Embodiment 15

[0139] The difference from Example 2 is that the content of the solid electrolyte LLZO is adjusted to 40 mass %.

[0140] Example 16

[0141] The difference from Example 2 is that the content of the solid electrolyte LLZO is adjusted to 30 mass %.

[0142] Embodiment 17

[0143] The difference from Example 2 is that the content of the solid electrolyte LLZO is adjusted to 20 mass %.

[0144] Embodiment 18

[0145] The difference from Example 2 is that the content of the solid electrolyte LLZO is adjusted to 10 mass %.

[0146] Embodiment 19

[0147] Different from Example 1, the substrate is changed to a copper-lithium composite strip, wherein the thickness of the copper foil is 6 μm, the thickness of the single-sided lithium foil is 100 μm, and the positive electrode uses an untreated sulfur positive electrode sheet.

[0148] Embodiment 20

[0149] Different from Example 2, the substrate is changed to a copper-lithium composite strip, wherein the thickness of the copper foil is 6 μm, the thickness of the single-sided lithium foil is 100 μm, and the positive electrode uses an untreated sulfur positive electrode sheet.

[0150] Embodiment 21

[0151] The positive electrode sheet in Example 1 and the negative electrode sheet in Example 19 are used to assemble a soft-pack battery.

[0152] Comparative Example 1

[0153] The sulfur cathode preparation method refers to Example 1. The protective layer is formed as follows.

[0154] PVDF powder was placed in a porcelain boat, placed in a plasma generator, and evacuated to 10 -3 Pa, turn on the plasma generator power, the carrier gas is argon, wait for 5 minutes, turn on the electron beam evaporation equipment to modulate the current to 4A, adjust the voltage to about 1kV, use the sulfur positive electrode prepared as above as the substrate, control its temperature to room temperature, the substrate distance is 50mm, deposit for 0.5h, take out the sample after completion, and refer to Example 1 for the battery preparation process. However, since the sulfur positive electrode coating only has a polymer film, the lithium ion conductivity of the coating of this structure is low, so the internal resistance of the battery is large, the rate performance is seriously affected, the battery polarization is large, and the comprehensive electrochemical performance of the battery is seriously affected.

[0155] The difference from Example 1 is that the LLZO content is reduced to 0.

[0156] Comparative Example 2

[0157] The sulfur cathode preparation method refers to Example 1. The protective layer is formed as follows.

[0158] LLZO powder was placed in a porcelain boat, placed in a plasma generator, and evacuated to 10 -3 Pa, turn on the plasma generator power, the carrier gas is argon, wait for 5 minutes, turn on the electron beam evaporation equipment, the current modulation is 4A, the voltage is adjusted to about 1kV, the sulfur positive electrode sheet is used as the substrate, the temperature is controlled to be room temperature, the substrate distance is 50mm, the deposition is 0.5h, and the sample is taken out after completion. The battery preparation process refers to Example 1.

[0159] The difference from Example 1 is that the PVDF content is reduced to 0.

[0160] Comparative Example 3

[0161] The sulfur cathode preparation method refers to Example 1. The protective layer is formed as follows.

[0162] PVDF powder was dissolved in a mixture of DMSO / acetone (volume ratio 70 / 30) with a solid content of 2% by mass. The suspension system was stirred at a flow rate of 30 cm 3 / min, is brought into the plasma chamber by argon gas at a speed of 10 -3 Pa, the plasma torch energy is 50 kW, the sulfur positive electrode sheet is used as the substrate, the substrate distance is 30 mm, the deposition time is 0.5 h, and the battery preparation process refers to Example 1.

[0163] The difference from Example 2 is that the LLZO content is reduced to 0.

[0164] Comparative Example 4

[0165] LLZO powder was dissolved in a mixture of DMSO / acetone (volume ratio 70 / 30) with a solid content of 2% by mass. The suspension system was stirred at a flow rate of 30 cm 3 The argon gas is brought into the plasma chamber at a speed of 10 / min, and the chamber pressure is maintained at 10 -3 Pa, the plasma torch energy is 50kW, the lithium sheet with carbon film as the current collector is used as the substrate, wherein the thickness of the lithium sheet is 150μm, the substrate distance is 30mm, and the deposition is 0.5h to obtain the surface-protected lithium sheet. The battery preparation process refers to Example 1. Since the surface coating of the sulfur positive electrode sheet is only inorganic ceramic particles, the interface contact between the inorganic ceramic particles and the surface of the sulfur positive electrode is poor, resulting in weak lithium ion migration kinetics, reducing the battery rate performance, and the inorganic ceramic particles are easy to fall off on the surface and cannot play an effective protective role.

[0166] The difference from Example 2 is that the PVDF content is reduced to 0.

[0167] Comparative Example 5

[0168] Different from Example 19, the PVDF content was reduced to 0.

[0169] Comparative Example 6

[0170] Different from Example 19, the LLZO content was reduced to 0.

[0171] Comparative Example 7

[0172] Different from Example 20, the PVDF content was reduced to 0.

[0173] Comparative Example 8

[0174] Different from Example 20, the LLZO content was reduced to 0.

[0175] The batteries obtained in the above examples and comparative examples were tested for first cycle gram capacity and gram capacity after 20 cycles, and the results are shown in the following table.

[0176]

[0177]

[0178] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

[0179] Industrial Applicability

[0180] In the present invention, a protective layer formed of a polymer and an inorganic material is formed on a sulfur positive electrode and / or a metal lithium negative electrode, thereby solving the problems of polysulfide shuttling and the interface compatibility and low ion conductivity between the metal lithium negative electrode and the protective layer. When it is used for a sulfur positive electrode, the problem of polysulfide shuttling can be solved; when it is used for a lithium negative electrode, the problem of low ion conductivity and the interface compatibility between the metal lithium negative electrode and the protective layer can be solved.

Claims

1. An electrode, characterized in that: The invention comprises a sulfur positive electrode and a protective layer on the surface of the sulfur positive electrode, wherein the protective layer is formed of a composite material comprising a polymer and an inorganic material.

2. The electrode according to claim 1, wherein the polymer comprises one or more of fluoropolymers, polyethylene oxide, polyurethane, poly(meth)acrylates, polyacrylonitrile, polyethyleneimine, polyethylcyanoacrylate, polycarbonates, polymalonates, and polysuccinates.

3. The electrode according to claim 2, wherein the fluorine-containing polymer includes one or more of polyvinylidene fluoride, polyvinylidene fluoride, polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-chlorotrifluoroethylene, and perfluorosulfonic acid resin; the poly(meth)acrylates include one or more of polymethyl acrylate, polymethyl methacrylate, polyethyl acrylate, polyethyl methacrylate, polybutyl acrylate, and polybutyl methacrylate; the polycarbonates include one or more of polyvinylene carbonate, polypropylene carbonate, polytrimethyl carbonate, and polyethylene carbonate.

4. An electrode comprising a metallic lithium negative electrode and a protective layer on the surface of the metallic lithium negative electrode, characterized in that: The protective layer is formed of a composite material, the composite material includes a polymer and an inorganic material, and the polymer includes one or more of polyethyleneimine, polyethylcyanoacrylate, polymalonates, and polysuccinates.

5. The electrode according to claim 2 or 4, wherein the polymalonates include one or more of polypentylene malonate, polyethylene malonate, polypropylene malonate, and polyhexylene malonate; and the polysuccinates include one or more of polyethylene succinate, polypropylene succinate, polyethylene succinate, and polybutylene succinate.

6. The electrode according to any one of claims 1 to 5, wherein the inorganic material comprises an inorganic ceramic composite electrolyte, and the inorganic ceramic composite electrolyte comprises at least one of an oxide solid electrolyte and a sulfide solid electrolyte; Preferably, the oxide solid electrolyte is selected from one or more of lithium lanthanum zirconium oxide, lanthanum titanate lithium oxide, tantalum-doped lithium lanthanum zirconium oxide, aluminum-doped lithium lanthanum zirconium oxide, and lithium germanium aluminum phosphate; The sulfide solid electrolyte is selected from one or more of lithium germanium phosphorus sulfur compounds and lithium phosphorus sulfur chloride compounds.

7. The electrode according to any one of claims 1 to 6, wherein the inorganic material accounts for 5% to 95% by mass, preferably 70% to 90% by mass, of the total mass of the polymer and the inorganic material. 8 . The electrode according to claim 1 , wherein the protective layer has a thickness of 3 μm to 250 μm.

9. A sulfur positive electrode, comprising the electrode according to claim 1 and a positive electrode current collector, wherein the positive electrode current collector is aluminum foil, carbon-coated aluminum foil, porous aluminum foil or porous carbon-coated aluminum foil. 10 . A lithium negative electrode, comprising the electrode according to claim 4 and a negative electrode current collector, wherein the negative electrode current collector is a copper foil or a carbon film.

11. A method for preparing an electrode, characterized in that: It includes the following steps: Step S1, mixing a polymer and an inorganic material to prepare a composite material; and Step S2, forming a protective layer formed of the composite material on the surface of the metal lithium negative electrode or the sulfur positive electrode. 12 . The preparation method according to claim 11 , wherein in step S2 , the protective layer is formed by a solution method, a plasma deposition method, a magnetron sputtering method, a pulsed laser sputtering method, a physical deposition method or a chemical vapor deposition method.

13. The preparation method according to claim 12, wherein the solution method is selected from any one of a plasma gas spraying method, a compressed gas spraying method, a high pressure spraying method, and a plasma source evaporation solution method. The preparation method according to claim 12 , wherein the plasma deposition method is a suspension plasma deposition method or a plasma-assisted electron beam deposition method.

15. The preparation method according to claim 14, wherein in the suspension plasma deposition method, the suspension comprises the polymer, the inorganic material and a solvent; and the solvent comprises one or more of N,N-dimethylformamide, dimethyl sulfoxide and acetone.

16. The preparation method according to claim 14 or 15, wherein in the suspension plasma deposition method, the ejection speed of the suspension is 10-40 cm 3 / min; the distance between the plasma jet nozzle and the substrate is 20-150mm.

17. The preparation method according to any one of claims 14 to 16, wherein in the suspended plasma deposition method, the plasma is generated in any one of the following ways: DC glow discharge plasma, wherein the excitation power supply voltage is 500V-1500V; pulsed glow discharge plasma, wherein the pulse width is 30-150μs and the peak voltage is 400V-600V; dielectric barrier plasma, wherein the high-voltage excitation power supply is a sinusoidal AC power supply or a nanosecond pulse high-voltage power supply; radio frequency plasma, wherein the frequency of the AC glow discharge is higher than 100kHz, and the radio frequency plasma includes capacitively coupled radio frequency plasma and inductively coupled radio frequency plasma, wherein the discharge voltage of the inductively coupled radio frequency plasma and the capacitively coupled radio frequency plasma is 100V-1000V and the pressure is 1Pa-100Pa respectively; microwave plasma, wherein the microwave frequency of the plasma is 300MHz-10GHz.

18. The preparation method according to claim 14, wherein in the plasma-assisted electron beam deposition method, the target material is the composite material; the electron beam current is less than 5A, the voltage is less than 2kV, and the distance from the target material to the substrate is 5mm-100mm.

19. The preparation method according to claim 14 or 18, wherein in the plasma-assisted electron beam deposition method, the plasma source is selected from any one of the following: capacitively coupled plasma, wherein the frequency of the plasma generated is higher than 100kHz); DC glow discharge plasma, wherein the excitation power supply voltage is 500V-1500V; pulsed glow discharge plasma, wherein the pulse width is 30μs-150μs and the peak voltage is 400V-600V; dielectric barrier plasma, wherein the high-voltage excitation power supply is a sinusoidal AC power supply or a nanosecond pulse high-voltage power supply; microwave plasma, wherein the microwave frequency of the plasma generated is 300MHz-10GHz.

20. A lithium ion battery comprising the electrode according to any one of claims 1 to 10 or the electrode prepared by the preparation method according to any one of claims 11 to 19.

Citation Information

Patent Citations

  • Lithium secondary battery

    CN110651389A

  • Composite lithium negative electrode, preparation method thereof and lithium battery

    CN110676433A

  • Metal lithium surface protection method

    CN113346052A

  • Composite lithium metal negative electrode material, preparation method thereof and solid-state battery

    CN116666577A

  • Non-aqueous electrolyte secondary battery

    JP2003242964A